Aujeszky’s Disease and the Development of the Marker/DIVA Vaccination Concept - Thomas C. Mettenleiter (Pathogens, 2020)
Aujeszky’s disease or pseudorabies is an infection of animals caused by Suid alphaherpesvirus 1, also designated as pseudorabies virus (PrV). Whereas many mammals are susceptible to PrV, only pigs are able to survive productive infection. Early reports on this disease originate from cattle and companion animals with the hallmark sign of “mad itch”, meaning development of pruritus. Although first reports date back to the early 19th century, it was Aladár Aujeszky who in 1902 described this disease, which has since been named after him, as a separate entity. AD expanded in the 20th century, despite efforts to control this infection in the growing pig farming industry. Live-attenuated vaccines were developed in the early 1960s, which assisted early eradication efforts. A major breakthrough in animal vaccinology occurred in the mid-1980s, when it was found that several live-attenuated PrV vaccine strains lacked a significant portion of the genome, including the gene encoding a major immunogenic viral envelope glycoprotein. Upon the development of a suitable serological assay, the first marker vaccine/DIVA concept (differentiating infected from vaccinated animals) was developed. Moreover, the first genetically modified live vaccines emanated from molecular work on PrV. Thus, AD serves as a hallmark for the history of veterinary virology as well as for pioneering novel strategies for controlling animal infectious diseases.